Performance Of GPS For Road Network Mapping And Analyzing Vehicle Position - Mohamad Tajudin, Nizar Alwi (Universiti Sains Malaysia, 2006)
The main objective object of this project is to determine the performance of Global Positioning System (GPS) in road network mapping and to analyze the vehicle position. The road network near the USM Engineering campus has been chosen as a study location. Today GPS is a very popular and useful in the field of surveying and navigation. Many GIS software can be used in GPS measurement technique and it also can be integrated with GPS data, whereby giving useful information. GIS also can be use to created a dynamic map where, the map that being create can be filled with any information or attribute data. GIS map (dynamic) also can be updated and also correction can be made to the map. ArcView GIS version 3.1 can be used to visualize, explore, query and analyze data spatially. In this project the Omnilite Reciever 132 and Psion Workabout Data logger is used to collect the road network data. ArcView GIS version 3.1 is used to analyze the data and also in mapping the road network of the study area. Coordinate and time data can be obtained from GPS instrument. Vehicle speed can be computed using this GPS data, so an analysis of vehicle speed on the area can be made.